Business statistics : for contemporary decision making - Black, Ken (Kenneth Urban) (Hoboken : Wiley, 2020)
"The tenth edition of Business Statistics for Contemporary Decision Making continues the tradition of presenting and explaining the concepts and principles of business statistics through the use of clear, complete, student-friendly pedagogy within the context and framework of business analytics. The author and Wiley have vast ancillary resources available through WileyPLUS with which to complement the text in helping instructors effectively deliver this subject matter and in assisting students in their learning. With WileyPLUS instructors have far greater latitude in developing and delivering their course than ever before. a number of important changes and additions to the tenth edition. edition have been updated and changed as needed to reflect today's business world. To meet the challenges, opportunities, and potentialities presented to business decision makers through the advent of big data, a new field of business methodology and quantitative investigation, business analytics, has arisen. Realizing the potential of this new approach, we have infused the tenth edition with the language of business analytics along with its definitions, approaches, and explanations to better assist the student in understanding business analytics and the role that business statistics plays in it"--
Revised edition of the author's Business statistics, 2016.
Includes index.
Keywords: Commercial statistics